Controlled Delivery of MicroRNAs into Primary Cells Using Nanostraw Technology. Issue 6 (3rd May 2021) - Pop, Mara A.; Almquist, Benjamin D.
Abstract : MicroRNAs (miRNAs) are small noncoding RNAs that play key roles in posttranscriptional gene regulation. Being involved in regulating virtually all cellular processes, from proliferation and differentiation to migration and apoptosis, they have emerged as important epigenetic players. While most interest has gone into which miRNAs are involved in specific cellular processes or pathologies, the dosage‐dependent effects of miRNAs remain vastly unexplored. Different doses of miRNAs can cause selective downregulation of target genes, in turn determining what signaling pathways and cellular responses are triggered. To explore this behavior, the effects of incremental miRNA dosage need to be studied; however, current delivery methods for miRNAs are unable to control how much miRNA enters a cell. Herein, an approach is presented based on a nanostraw–electroporation delivery platform that decouples the delivery from biological mechanisms (e.g., endocytosis) to enable precise control over the amount of miRNA delivered, along with demonstrating ratiometric intracellular delivery into primary dermal fibroblasts for miR‐181a and miR‐27a. In addition, it is shown that the nanostraw delivery platform allows efficient delivery of miRNAs into primary keratinocytes, opening new opportunities for successful miRNA delivery into this hard‐to‐transfect cell type. Abstract : MicroRNAs (miRNAs) are small noncoding RNAs that impact posttranscriptional gene regulation. Interestingly, different doses of miRNAs can selectively downregulate targeted genes. However, current delivery methods for miRNAs cannot control how much miRNA enters a cell. Herein, a nanostraw device enables miRNA dosage control, ratiometric intracellular delivery into primary human fibroblasts of multiple miRNAs, and efficient delivery into primary human keratinocytes.